STEGANOGRAFI AUDIO (WAV) MENGGUNAKAN METODE LSB (LEAST SIGNIFICANT BIT) - Sugeng Santoso; Arisman Arisman; Windy Sentanu (CCIT Journal, 2016)
Security of distributed information is essential for maintaining the confidentiality of the information. The process of securing is done by hiding the information on other digital media that are not visible existence. This technique is called steganography, the art of hiding data into digital media with a particular method so that other people do not realize there is something in the digital media. In this paper conducted a study to hide information into digital audio file is not compressed (. Wav) as a carrier file using the Least Significant Bit Modification. Least Significant Bit Modification is a method of hiding information by modifying the last bits of carrier files with the bits of information and only cause changes in the value of a bit higher or a lower one. The system was designed with two main processes, namely phase Embedding and Extracting stage